The Riace Bronzes. Recent Research and New Scientific Knowledge - Castrizio, Daniele (Actual Problems of Theory and History of Art, 2019)
It is necessary to highlight how the recent analyses on the casting materials of the two Riace statues have demonstrated that the two Bronzes were made in Argos, in the Peloponnese, in the same period and in the same workshop. These results must be included in any discussion of the Riace Bronzes.In our paper, we identify the Bronzes with the famous Fratricides group by Pythagoras of Rhegion. To support this case, we can now rely on another element of clarification: the “Lille Papyrus”. A fragment of Stesichorus survives, with an extraordinary stroke of luck. This passage offers us the speech that the mother of Eteocles and Polynices addresses to her sons who are about to confront each other in a mortal duel. The scene can be correlated very closely with the stance and characteristics of the Riace Bronzes. We can even see these statues as actors on a stage! A concept of art that seems highly modern, but still dates back to the Severe Style, the first period in which the Greeks created an art of perfect mimesis, imitation of reality.
Keywords: Greek archaeology; iconography; Greek art; bronzes of Riace; Greek sculpture